A confluence of evidence: What lies behind a "whole school" approach to health education in schools?. Issue 2 (1st February 2016) - Thomas, Felicity; Aggleton, Peter
Abstract : Purpose: – The purpose of this paper is to contribute to the evidence base to support whole school approaches. Design/methodology/approach: – The authors conduct a review of published evaluations and evidence syntheses across six areas in the international health-promoting schools literature. Findings: – Although whole school approaches are often advocated in literature and policy on health-promoting schools, the evidence base for their effectiveness is partial and is often health topic specific. This paper reviews the evidence base across six different health-related areas, namely: sexual health; bullying; alcohol and drug use; mental health; school connectedness; and access to services. It identifies commonalities in learning, enabling a confluence of evidence on the factors central to the provision of effective health education and support within schools. Whilst findings endorse a whole school approach, they also suggest that some of the more subtle evidence-based principles on which such approaches are underpinned are not generally explicitly reflected in practice. Originality/value: – The paper offers the first cross-topic synthesis of findings on health education effects and effectiveness in six health-related areas, to identify commonalities in learning. Findings contribute to the evidence base for the use of a whole school approach when undertaking health education in schools.